Detection of leptospiral DNA in rat kidney and environmental samples using loop-mediated isothermal amplification - Lee, Pui Yuei (2019)
Leptospirosis is regarded as one of the most widespread zoonotic disease which is caused by the pathogenic Leptospira spp. Rodents are important reservoirs for human leptospirosis while environmental samples plays an important role as source of infection to human and animals. A rapid and robust detection of Leptospira is essential to reduce avoidable leptospirosis death substantially. Hence, this study aims to detect the presence of Leptospira targeting secY gene in rat kidney and environment samples using loopmediated isothermal amplification (LAMP). Rat kidney samples were obtained from leptospirosis outbreak areas and hot spot area while environmental samples were obtained from leptospirosis outbreak areas. A total of 150 rat kidney samples and 46 environment samples consisting of 22 water samples and 24 soil samples were used in this study. DNA extraction was performed in rat kidney samples using commercially available extraction kit while direct boiling method was used for environment samples. All isolated DNA samples were subjected to LAMP assay targeting secY gene which was performed for 30 minutes at 65°C. PCR was performed on all isolated DNA samples using LAMP outermost primers (F3 and B3) to compare the analytical sensitivity of these two nucleic acid detection methods. The presence of secY gene was confirmed by sequencing on selected PCR positive samples. Leptospiral DNA was detected from 56 out of 150 (37.3%) rat kidney samples using LAMP while 28 out of 150 (18.7%) were detected using PCR. For environment samples, leptospiral DNA was detected from 4 out of 22 (18.9%) water samples and 14 out of 24 (58.3%) soil samples using LAMP and none of the environment samples were detected positive using PCR. LAMP system targeting secY gene showed higher detection rate compared to PCR in rat kidneys particularly for environment samples. The Bst DNA polymerase used in the LAMP system was reported to be more tolerable to inhibitors than Taq DNA polymerase used in PCR. LAMP also showed to have better sensitivity compare to PCR and these may explain the higher detection rate in LAMP compared to PCR in this study. The LAMP assay was further modified to investigate the stability of the premixed LAMP stored at room temperature. The premixed LAMP was stable up to 45 days without losing the activity when stored at room temperature in the presence of sucrose. In conclusion, LAMP offered better detection compared to PCR for its simplicity, rapidity and higher detection rate. The addition of sucrose in reaction mixture allowed the premixed reagent to be stored at room temperature which is helpful in field testing during outbreak where cold storage is not available.